Association of polymorphism in glutamate-cysteine ligase catalytic subunit gene with schizophrenia: A case-control study in a Tunisian population - Raffa, Monia; Jrad, Besma Bel Hadj; Khelil, Amel Haj; Kerkeni, Abdelhamid; Mechri, Anwar (Gene reports, 2016)
Glutathione (GSH) is a key regulator of oxidative balance in all mammals, especially in the central nervous system. The first step of glutathione synthesis is catalysed by glutamate cysteine ligase (GCL), which is composed of catalytic and modifier subunits (GCLC and GCLM, respectively). The purpose of this study was to test the hypothesis that the -129C/T polymorphism in the promoter region of the glutamate-cysteine ligase catalytic subunit (GCLC) gene may be associated with the schizophrenia disease and if this polymorphism could affect plasma GSH concentrations. The GCLC -129C/T genotypes were determined in 138 schizophrenic patients and 123 healthy individuals using a PCR-based restriction fragment length polymorphism (RFLP) method. Glutathione levels: total glutathione (GSHt), reduced glutathione (GSHr) and oxidized glutathione (GSSG) were determined by spectrophotometry. The subjects with -129C/T and T/T genotypes are highly associated with schizophrenia. No association was found between glutathione levels and the -129C/C genotype, C/T and T/T genotypes in schizophrenic patients. The present finding indicated that the GCLC polymorphism seems to be associated with schizophrenia disease in at least a Tunisian population.